Stalker, de Andrei Tarkovski - as semelhanças e dessemelhanças com Piquenique à Beira da Estrada, de Arkadi e Boris Strugatski - Delfini, Paulo Afonso Monteiro (Universidade Federal de São Carlos, 2018)
The present dissertation aims to carry out a study on the process of written translation for audiovisual between two languages: Literature and Cinema, with the object of the novel Roadside Picnic (1972) by Brothers Arkadi and Boris Strugatski and their translation to the cinema: the film Stalker (1979) by Andrei Tarkovski. For this, a detailed analysis of both works was established as a procedure, highlighting the similarities and, as an intermediate stage, the script of the film to identify the dissimilarities. The theoretical bias used for this work is based on the studies of Haroldo de Campos on transcription, re-creation and poetic translation, as well as the theories of Julio Plaza on Intersemiotic Translation. We will also work on the film elements approached through cinematographic language to perform analyzes and thus better understand the style and poetic optics of Andrei Tarkovski and his other relations with the narrative of the work. At a last moment the analyzes will have as an intention the understanding of the temporal and spatial construction making a parallel between the narratives of the literary work and the cinematographic work.
Keywords: Transcriação; Pocesso criativo; Transcreation; Creative process; Tarkovski, Andrei Arsenevich, 1932-1986; Stalker; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS